Tax expenditure and economic growth of the fishing sector in Peru - Chung Sánchez, Kenji Alberto (2023)
Objective: To determine the relationship between tax expenditure and economic growth in the Peruvian fishing sector. Methods: The research was quantitative approach, correlational level and retrospective and cross-sectional in design. Public sources covering the period from 2005 to 2022 were used for data, and a non-experimental analysis was employed along with Pearson's correlation coefficient statistical model. Results: The analysis revealed an important variability in the GDP of the fishing sector; however, there was a lack of a significant correlation between the tax expenditure of the sector and its GDP. Conclusion: The study suggests that while the GDP of the fishing sector experienced fluctuations along with tax refunds, tax expenditures may have limited or no influence on the sector's economic growth.